Zero-crossing algorithm for the demodulation of FBGs inscribed in gradient index multimode fibres - Theodosiou, Antreas; Kalli, Kyriacos; Komodromos, Michael (My University, 2018)
We present a method to demodulate multiple-peak fibre Bragg gratings inscribed in a gradient index multimode fibre. The algorithm combines the cross-correlation method with the Hilbert transformation. The proposed algorithm was simulated and evaluated experimentally.
Keywords: Demodulation; Fiber Bragg gratings; Fiber optic sensors; Mathematical transformations; Optical fibers; Zero-crossings